The Effect of Work life Balance and Employee Engagement on Work Professionalism for Female Teachers at SMAN 5 Tasikmalaya - Yuliani, Lia; Hermina, Nurul (Universitas Pamulang, 2022)
Currently, working women have become commonplace. Women do not only do activities at home but also do activities outside the home to work and earn income. The purpose of this study was to determine the effect of work-life balance and employee engagement on the professionalism of female teachers. The research method used was descriptive and verified with a population of 45 people, while the sampling method used a saturated sample so that the number of research samples was the same as the total population. This research was conducted at SMAN 5 Tasikmalaya. The result of the research is that it is found that work-life balance has a positive effect on work professionalism. The next finding is the effect of employee engagement on work professionalism for female teachers. The last finding is that there is a joint positive influence on work-life balance and employee engagement on the professionalism of teachers' work.